Computational and experimental study of shock wave interactions with cells - Li, D (2016)
This thesis presents a combined numerical and experimental study on the response of kidney cells to shock waves. The motivation was to develop a mechanistic model of cell deformation in order to improve the clinical use of shock waves, by either enhancing their therapeutic action against target cells or minimising their impact on healthy cells. An ultra-high speed camera was used to visualise individual cells, embedded in tissue-mimicking gel, in order to measure their deformation when subject to a shock wave from a clinical shock wave source. Advanced image processing was employed to extract the contour of the cell from the images. The evolution of the observed cell contour revealed a relatively small deformation during the compressional phase and a much larger deformation during the tensile phases of a shock wave. The experimental observations were captured by a numerical model which describes the volumetric cell response with a bilinear Equation of State and the deviatoric cell response with a viscoelastic framework. Experiments using human kidney cancer cells (CAKI-2) and noncancerous kidney cells (HRE and HK-2) were compared to the model in order to determine their mechanical properties. The diﬀerences between cancerous and noncancerous cells were exploited to demonstrate a design process by which shock waves may be able to improve the speciﬁcity on targeted cancer cells while having minimal effect on normal cells. The cell response to shock waves was studied in a more biophysically realistic environment to include inﬂuence of cell size, shape and orientation, and the presence of neighbouring cells. The most signiﬁcant diﬀerence was predicted when cells were in a cluster in which case the presence of neighbouring cells resulted in a four-fold increase on the von Mises stress and the membrane strain. Finally the numerical model was extended to capture the effect of cell damage using one of two paradigms. In the ﬁrst paradigm the model captured microdamage during one shock wave but then assumed that the cell recovered by the time the next shock wave arrived. The second model allowed microdamage to accumulate with increasing number of shock waves. These models may be able to explain the strong effect that shock wave loading rate has on tissue damage. In conclusion a validated numerical model has been developed which provides a mechanistic understanding of how cells respond to shock waves. The model has application in suggesting improved strategies for current uses of shock waves, e.g., lithotripsy, as well as opening up new indications such as cancer treatment.